Contextualizing narratives of Geography's past, present, and future: Synthesis, difference, and cybernetic control. Issue 1 (March 2022) - Grove, Kevin; Rickards, Lauren
In this article, we seek to open up for critical debate disciplinary narratives that center the "synthesis" qualities of geographic thought. Proponents of Geography often emphasize its integrative, synthesis approach to human–environment relations to underline its value to interdisciplinary research initiatives addressing critical real-world issues such as climate change. But there are multiple styles of knowledge synthesis at work within academia and beyond, and they have contradictory ethical and epistemological effects. More specifically, synthesis is on the rise, but it is not Geography's synthesis-as-understanding. Rather, an increasingly dominant cybernetic sociotechnical imaginary is installing a specific notion of synthesis—"synthesis-as-solution"—into universities, transforming both the production of knowledge and the institutional management and technological manifestation of that production. This cybernetic sociotechnical imaginary constrains research ethically and epistemologically to reduce knowledge to the synthesizable information flows and continuous innovation that characterize cybernetic control. In this context, non-conforming research—that is, research that disrupts or disdains such smooth synthesis—risks being labeled unprofessional, unimportant, and obsolescent and marginalized institutionally. Geographic disciplinary narratives that unreflexively celebrate synthesis thus risk producing a paradoxical future for Geography, one in which more space for different modes of knowledge production is created, but the type of difference recognized and affirmed is severely constrained. There is a pressing need for geographers to pay more attention to the practices and contexts in which we create disciplinary narratives because, like the content of our knowledge production, they can either challenge or reinforce a cybernetic sociotechnical imaginary.